2018
DOI: 10.1016/j.omtn.2018.08.009
|View full text |Cite
|
Sign up to set email alerts
|

miR-17-3p Downregulates Mitochondrial Antioxidant Enzymes and Enhances the Radiosensitivity of Prostate Cancer Cells

Abstract: Radioresistance remains to be a major obstacle in the management of patients with advanced prostate cancer (PCa). We have identified a mature miR-17-3p processed from the 3′ arm of precursor miR-17, which appeared to be able to inhibit three major antioxidant enzymes located in mitochondria, i.e., manganese superoxide dismutase (MnSOD), glutathione peroxidase 2 (Gpx2), and thioredoxin reductase 2 (TrxR2). Here we show that upregulation of miR-17-3p remarkably sensitized PCa cells to ionizing radiation (IR). Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 49 publications
0
55
0
Order By: Relevance
“…However, radioresistance is a major challenge that limits the efficacy of radiotherapy (Chang et al, ). Emerging evidence indicate that miRNAs could influence the radiosensitivity of various cancer cells through interplaying with other biological processes such as cell proliferation, apoptosis, cell cycle checkpoints, autophagy, and so forth (Palacios et al, ; Pawlik & Keyomarsi, ; Shao et al, ; Xu et al, ). Thus we performed human miRNA probe hybridization chip analysis to examine the expression profiles of miRNA in LNCaP cells which were exposed to X‐rays and 12 C 6+ ions.…”
Section: Discussionmentioning
confidence: 99%
“…However, radioresistance is a major challenge that limits the efficacy of radiotherapy (Chang et al, ). Emerging evidence indicate that miRNAs could influence the radiosensitivity of various cancer cells through interplaying with other biological processes such as cell proliferation, apoptosis, cell cycle checkpoints, autophagy, and so forth (Palacios et al, ; Pawlik & Keyomarsi, ; Shao et al, ; Xu et al, ). Thus we performed human miRNA probe hybridization chip analysis to examine the expression profiles of miRNA in LNCaP cells which were exposed to X‐rays and 12 C 6+ ions.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of antioxidant molecules in tumors have been identified as factors that make antitumor therapy difficult in many previous studies [44,45]. erefore, targeting antioxidant mechanisms might be a good therapeutic strategy for efficient radiotherapy [46]. Recent studies have reported that antioxidant mechanisms can be regulated by mTOR signaling [47][48][49].…”
Section: Introductionmentioning
confidence: 99%
“…Major mitochondrial antioxidant enzymes, including SOD and Gpx2, have been shown to be inhibited by miR-17 [149]. Furthermore, studies unveiled that miR-17, upregulated through inflammatory processes [150], is involved in the pathogenesis of endothelial dysfunction in the context of obesity and diabetes [151,152].…”
Section: Oxidative Stress and Mirnasmentioning
confidence: 99%
“… Target Refs. miR-210 Unknown EC apoptosis and atherosclerosis [ 125 ] ISCU 1,2 [ 124 ] miR-21 Up [ 130 , 131 ] Promotes ROS production [ 132 , 133 ] SOD [ 132 , 133 ] miR-551b Up [ [ 140 ] Enhances ROS accumulation [ 134 , 135 ] CAT, SOD [ 134 , 135 ] miR-200c Up [ 142 , 143 ] EC apoptosis, ROS accumulation and senescence [ 144 , 145 ] PRDX2 [ 144 ] miR-17 Up [ 151 , 152 ] EC dysfunction [ 151 , 152 ] SOD, Gpx2 [ 149 ] miR-23b Up [ ...…”
Section: Obesity Micrornas and Endothelial Dysfunctionmentioning
confidence: 99%